Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3390/w7073320
|View full text |Cite
|
Sign up to set email alerts
|

Runoff Response to Climate Warming and Forest Disturbance in a Mid-Mountain Basin

Abstract: A headwater basin in the Sumava Mountains (Czech Republic), the upper Vydra basin, has undergone forest disturbance as a result of repeated windstorms, a bark beetle outbreak, and forest management. This study analyzed the long-term hydro-climatic changes by using a combination of statistical analyses, including Mann-Kendall tests, CUSUM analysis, Buishand's and Petitt's homogeneity tests, and Kriging. Although the runoff balance over the study period experienced no apparent changes due to climate warming and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 46 publications
2
38
1
Order By: Relevance
“…Berghuijs et al (2014) showed that a higher fraction of precipitation fallen as snow is associated with higher long-term mean streamflow in comparison to catchments with lower snowfall fraction. Higher air temperatures during spring affect the onset of snowmelt in streamflow shifting it towards earlier spring (Barnett et al, 2005;Godsey et al, 2014;Langhammer et al, 2015;Ledvinka, 2015). These changes lead to a higher fraction of annual flow occurring earlier in the water year as evident from many studies across the western United States (Cayan et al, 2001;Stewart et al, 2005;Day, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…Berghuijs et al (2014) showed that a higher fraction of precipitation fallen as snow is associated with higher long-term mean streamflow in comparison to catchments with lower snowfall fraction. Higher air temperatures during spring affect the onset of snowmelt in streamflow shifting it towards earlier spring (Barnett et al, 2005;Godsey et al, 2014;Langhammer et al, 2015;Ledvinka, 2015). These changes lead to a higher fraction of annual flow occurring earlier in the water year as evident from many studies across the western United States (Cayan et al, 2001;Stewart et al, 2005;Day, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…Additionally, ongoing climate changes and consequent changes of winter and spring runoff represent positive feedback and might further underline the impact of land cover changes on runoff (Blahušiaková and Matoušková, 2015;Langhammer et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…The study area of the Roklanský Brook and the experimental subcatchments is located at the headwaters of the Sumava Mountains, Central Europe (Figure 1), and features an elevated montane plain with moderate hillslopes [13]. The area is homogeneous in terms of physiography.…”
Section: Study Areamentioning
confidence: 99%